First Report of Bronchial Oestriasis in a Domestic Dog - Filippo Maria Dini; Fabiano Raponi; Flavio Vallone; Roberta Galuppi; Fabio Macchioni (Veterinary Medicine and Science)
ABSTRACT This study reports the first case of bronchial myiasis in a dog caused by Oestrus ovis, a parasite known to infest sheep, and occasionally other mammals. A 9‐year‐old dog, from a rural area near Ancona (Italy), exhibited persistent coughing despite antibiotic and anti‐inflammatory treatments. Bronchoscopy revealed a live first‐instar larva of O. ovis, confirmed through morphological and molecular analyses. Larval removal and treatment with isoxazolines resulted in a rapid resolution of symptoms. This case highlights the critical importance of including atypical parasitic infestations in the differential diagnosis of respiratory symptoms in dogs. It underscores the importance of heightened vigilance, particularly in areas with sheep flocks, to prevent and manage such infestation effectively.